TINJAUAN SISTEMATIS TENTANG CHATGPT DALAM PENDIDIKAN BAHASA INGGRIS: PELUANG DAN TANTANGAN: PELUANG DAN TANTANGAN - Salsadila, Silva; Yasmin, Devita Aura; Tarihoran, Nafan (JEDLISH : Journal Of Education and English Language Teaching, 2025)
Advances in artificial intelligence (AI) have brought about significant changes in English Language Teaching (ELT). ChatGPT, as a language-based AI model, offers various benefits to students, such as improving writing skills, providing instant feedback, as well as supporting independent learning. However, its use also presents challenges, such as the risk of dependency, potential plagiarism, as well as a lack of digital literacy in assessing the credibility of information. This study aims to analyze students' and lecturers' perspectives on the use of ChatGPT in ELT. The method used was Systematic Literature Review (SLR) with PRISMA approach, analyzing 17 articles from Mendeley, ERIC, and Taylor & Francis databases. The results showed that ChatGPT changes the role of lecturers from material deliverers to facilitators who guide students in using AI critically and ethically. Although it can help with the preparation of teaching materials and evaluation, the implementation of this technology requires clear academic policies and digital literacy training for educators. The findings provide insights for educators and institutions in optimizing the use of ChatGPT in ELT to be more effective and ethical.